VERSION OF A MATHEMATICAL MODEL OF PURGE VENTILATION SYSTEM WITH A COMPLEX RECUPERATIVE HEAT EXCHANGER - Ezhov, Vladimir Sergeevich; Evgenievna, Semicheva Natalia; Nikolaevich, Tyutyunov Dmitry; Petrovich, Burtsev Alexey; Sergeevich, Perepelitsa Nikita (Journal of Applied Engineering Science, 2021)
The aim of the study is to develop a design of an air-heating recuperator for a purge ventilation system of a building inbuilt for the purpose of utilizing lower-grade heat from ventilation gases and emissions with the associated production of thermoelectricity. An experimental design of an air-heating recuperator as part of an experimental purge unit has been developed. It includes a thermoelectric source of electromotive difference, which operates as a result of the associated conversion of heat into electricity, which allows utilizing lower-potential heat of ventilation releases from 40 ° C to 60 ° C.
Keywords: purge unit; utilization; heat transfer coefficient; electric power; efficiency; autonomy; ventilation gases; thermoelectricity